Women are the Better Halves: Gender-based Variations in Virtues and Character Strengths. (May 2022) - Husain, Waqar
Several feminists have been arguing on the superiority of women over men. This debate, instead of being biological, revolves around the gender roles and moral characteristics of humans, based on which women have been regarded better than men. The current study supported this claim by involving 620 participants, including men and women. Character Strengths Rating Form (Ruch et al., 2014) was used to obtain data. Women projected significantly higher levels on a variety of character strengths as compared to men. The results revealed that women had significantly higher levels of wisdom, justice, curiosity, love of learning, social intelligence, leadership and appreciation of beauty and excellence. The overall picture confirmed women to be more virtuous than men.